SIME - An analytical method for evaluating emotional responses in Human-Computer Interaction - Santos, Maria Carolina De Souza; Silva, Leticia Zacano; Rodrigues, Kamila Rios da Hora; Neris, Vânia Paula de Almeida (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
Emotion is an important factor in Human-Computer Interaction (HCI) as it influences users’ behavior and satisfaction. Empirical methods, i.e., when users are directly involved, are often applied to assess emotional responses evoked by the user interface, but the cost of data collection and analysis is generally high. The adoption of analytical methods is an alternative to the high cost. Although analytical methods are widely accepted in HCI, analytical evaluations for emotional responses are lacking. The proposed analytical method in this work adopts the semiotic framework and Peirce’s ten classes of signs for the analysis of the design proposal and by the Scherer’s Semantic Space of Emotions for the association of possible emotional responses evoked by the interface signs. The current version of the proposed method was applied to a case study, and results were considered consistent when compared with those obtained through empirical methods.